New approaches to the study of localization of carbonaceous deposits on acidic zeolites - Охріменко, М.В.; Іваненко, В.В.; Волошина, Ю.Г.; Патриляк, К.І.; Патриляк, Л.К. (Proceedings of National Aviation University (archive), 2009)
The discrete-successive coke micro oxidation (DSCMO) method has been improved in the direction of its sensibility increase. Two acid catalysts on the base of NaX zeolite, modified by mint of SiCl4 for the purpose of deactivating the outer surface of zeolite crystals, have been synthesized. The samples were deactivated in the reaction of isobutane with isobutene alkylation. The coke formed has been investigated by the use of improved DSCMO method. It has been shown that coke of different H/C ratios burning down alternates with burning of pure carbon, and on these grounds a conclusion has been drawn about the successive burning of carbonaceous deposits on the outer surface of zeolite crystals, in the great cavities, sodalite cells, and finally in the hexagonal prisms.